THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE, ENVIRONMENTAL DISCLOSURE AND ENVIRONMENTAL COST ON ECONOMIC PERFORMANCE - Irfansyah Irfansyah; Husnah Nur Laela Ermaya; Krisno Septyan (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2018)
This research aims to examine the effect of environmental performance measured with PROPER, environmental disclosure measured with GRI index version 4.0, and environmental cost measured by comparing the cost incurred for CSR and net income. The populations in this study are agriculture, mining, manufacturing and other non- financial service companies listed in Indonesia Stock Exchange in 2013-2016 with 58companies in number. This study used purposive sampling method, leaving 15 companies that match the criteria. Hypothesis testing in this study used Multiple Linear Regression. The results of the testing showed that (1) environmental performance had significant effect on economic performance (2) environmental disclosure had no significant effect oneconomic performance (3) environmental cost had significant negative effect on economic performance. From Adjusted R square test result it showed independence of environemntal performance, environmental disclosure and environmental cost only being able to influence the dependent variable of economic performance with 15,6% inpercentage. Meanwhile, the rest of the percentage 84,4% was determined by other variables not included in this study.